Detection of comorbidities and synchronous primary tumours via thoracic radiography and abdominal ultrasonography and their influence on treatment outcome in dogs with soft tissue sarcomas, primary brain tumours and intranasal tumours1. (23rd August 2013) - Bigio Marcello, A.; Gieger, T. L.; Jiménez, D. A.; Granger, L. Abbigail
Abstract Canine soft tissue sarcomas (STS), primary brain tumours and intranasal tumours are commonly treated with radiotherapy (RT). Given the low metastatic potential of these tumours, recommendations regarding imaging tests as staging are variable among institutions. The purpose of our study was to describe thoracic radiographic and abdominal ultrasonographic findings in dogs with these neoplasms and to investigate association of abnormal findings with alterations in recommended treatment. Medical records from 101 dogs, each having thoracic radiographs and abdominal ultrasound performed as part of their staging, were reviewed. In 98 of 101 (97%), imaging abnormalities were detected, 27% of which were further investigated with fine needle aspiration cytology or biopsy. Nine percent of the detected abnormalities were considered serious comorbidities that altered treatment recommendations, including 3 (3%) which were confirmed as synchronous primary neoplasms. These findings may influence recommendations regarding the decision to perform thoracic radiographs and abdominal ultrasound prior to initiation of RT.